2021
DOI: 10.1109/tlt.2021.3056038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Ambient Learning Display on Noise Levels and Perceived Learning in a Secondary School

Abstract: Recent reviews addressing the impact of noise exposure in teaching and learning situations conclude negative effects on learning performance. Providing objective real-time feedback on noise is key for teachers and students to adjust it into suitable levels. This experimental work presents the results from a study exploring the visual feedback based on noise level and the impact on students' (n = 198) perceived learning performance collected in 24 sessions. The results suggest persuasive effects of the ambient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Speech 2008) Indoor 3-6 min L Aeq recordings in the center of the room with the students silent Avsar and Gonullu (2010) Outdoor 1 h L eq measurements 1.0 m from the wall and 1.20 m height Indoor unoccupied and occupied 10 min L Aeq measurements average of the front, middle and back row Çankaya Topak and Yılmazer (2022) Indoor unoccupied and occupied 40 min L Aeq recordings at the centre of the classroom and computer laboratory at a height of 100 cm for 9th-grade students and 110 cm for 10th-grade students Note that only the subjective ratings were used in the analysis, however Connolly et al (2013) Subjective ratings Goldschagg and Bekker (2020) Indoor unoccupied and occupied L Aeq recordings at least 1 m from the wall, on a tripod at the height of an average seated person's ear level. Time period not specified Note that only the subjective ratings were used in the analysis, however Minichilli et al (2018) Outdoor L Aeq,DAY recordings from 6am to 10 pm for 7 days at 1 m from the main outside façade of the school, at a height of 4 m Indoor 30 min L Aeq recordings at the centre of the classroom and 1 m from the open window Nelson et al (2020) Subjective ratings Persson and Hagquist (2021) Subjective ratings Tabuenca et al (2021) Mobile app collected 60 612 occupied samples every second over 24 sessions Note that only the subjective ratings were used in the analysis, however Wen et al (2019) Outdoor 20 min L Aeq, recordings made at four locations 1.5 m away from the outdoor walls and 1.2 m from the ground Indoor 20 min L Aeq, recordings made at three locations 1 m away from the indoor walls and 1.2 m from the ground with students silent Source: Authors' own creation F 42,5/6 intelligibility also increases as age increases for a given SNR. Hurtig et al (2016) found that second language listening comprehension was poorer when listening at a far versus close listening position.…”
Section: Discussionmentioning
confidence: 99%
“…Speech 2008) Indoor 3-6 min L Aeq recordings in the center of the room with the students silent Avsar and Gonullu (2010) Outdoor 1 h L eq measurements 1.0 m from the wall and 1.20 m height Indoor unoccupied and occupied 10 min L Aeq measurements average of the front, middle and back row Çankaya Topak and Yılmazer (2022) Indoor unoccupied and occupied 40 min L Aeq recordings at the centre of the classroom and computer laboratory at a height of 100 cm for 9th-grade students and 110 cm for 10th-grade students Note that only the subjective ratings were used in the analysis, however Connolly et al (2013) Subjective ratings Goldschagg and Bekker (2020) Indoor unoccupied and occupied L Aeq recordings at least 1 m from the wall, on a tripod at the height of an average seated person's ear level. Time period not specified Note that only the subjective ratings were used in the analysis, however Minichilli et al (2018) Outdoor L Aeq,DAY recordings from 6am to 10 pm for 7 days at 1 m from the main outside façade of the school, at a height of 4 m Indoor 30 min L Aeq recordings at the centre of the classroom and 1 m from the open window Nelson et al (2020) Subjective ratings Persson and Hagquist (2021) Subjective ratings Tabuenca et al (2021) Mobile app collected 60 612 occupied samples every second over 24 sessions Note that only the subjective ratings were used in the analysis, however Wen et al (2019) Outdoor 20 min L Aeq, recordings made at four locations 1.5 m away from the outdoor walls and 1.2 m from the ground Indoor 20 min L Aeq, recordings made at three locations 1 m away from the indoor walls and 1.2 m from the ground with students silent Source: Authors' own creation F 42,5/6 intelligibility also increases as age increases for a given SNR. Hurtig et al (2016) found that second language listening comprehension was poorer when listening at a far versus close listening position.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies gave feedback on participants' exposure indoors as well as outdoors. Most studies on noise exposure gave feedback about noise indoors, e.g., in the classroom [42][43][44] or a hospital [45][46][47]. These interventions aimed at lowering participants' voice, e.g., to protect the teacher's vocal health or intensive care patients.…”
Section: Descriptive Overview Of the Reviewed Studiesmentioning
confidence: 99%
“…Real-time feedback on noise exposure significantly decreased the noise level in hospitals [45, 46 and 47] and for air force workers experiencing continuous noise (but not for arms operators who experience impulse noise) [48]. Noise measurement devices in classrooms, indicating noise levels with colours and iconographs (smileys), resulted in a lower classroom noise level [42][43][44]. In one study, noisy classes had reversed effects because children tried to make loud sounds to keep the noise measurements up [44].…”
Section: Changes In Manifest Behaviourmentioning
confidence: 99%
See 2 more Smart Citations